Correction: The efficacy of pediatric elbow radiographic guidance in diagnosis of lateral humeral condyle fracture. - Satetha Vasaruchapong; Patarawan Woratanarat; Tanyaporn Patathong; Thira Woratanarat; Suphaneewan Jaovisidha; Chanika Angsanuntsukh (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0300014.].